Titanium dioxide fiber saturable absorber for Q-switched fiber laser generation in the 1-micrometer region - Harun, Sulaiman Wadi; Ab Rahman, Mohd Fauzi; Baharom, Mohamad Faizal; Mohd Rusdi, Muhammad Farid; Dimyati, Kaharudin; Pinninty, Harshavardhan Reddy; Paul, Mukul Chandra; Das, Shyamal; Dhar, Anirban; Abdul Latiff, Anas; Wang, Pengfei (Optica Publishing Group, 2019)
A passively Q-switched ytterbium-doped fiber laser (YDFL) operating at 1062 nm was demonstrated by using a segment of 20 cm titanium dioxide-doped fiber saturable absorber (TiO 2 DF SA). The Q-switched YDFL emerged stably with tunable repetition rates ranging from 32 kHz to 53 kHz as the pump power rose from 109 mW to 233 mW. Within this range of pump power, a maximum output power of 10.1 mW, maximum peak power of 75 mW, and maximum pulse energy of 191 nJ were obtained. The narrowest pulse width of 2.55 μs was attained at the maximum pump power of 233 mW, while the signal-to-noise ratio of the fundamental frequency was 47 dB. This demonstration reveals that the proposed TiO 2 DF SA is feasible for constructing a flexible and reliably stable Q-switched pulsed fiber laser in the 1-micrometer region.